Differential alternative polyadenylation landscapes mediate hematopoietic stem cell activation and regulate glutamine metabolism - Sommerkamp, Pia; Altamura, Sandro; Renders, Simon; Narr, Andreas; Ladel, Luisa; Zeisberger, Petra; Eiben, Paula Leonie; Fawaz, Malak; Rieger, Michael A.; Cabezas-Wallscheid, Nina; Trumpp, Andreas (Cell stem cell, 2020)
Alternative polyadenylation (APA) is emerging as an important regulatory mechanism of RNA and protein isoform expression by controlling 3′ untranslated region (3′-UTR) composition. The relevance of APA in stem cell hierarchies remains elusive. Here, we first demonstrate the requirement of the APA regulator Pabpn1 for hematopoietic stem cell (HSC) function. We then determine the genome-wide APA landscape (APAome) of HSCs and progenitors by performing low-input 3′ sequencing paired with bioinformatic pipelines. This reveals transcriptome-wide dynamic APA patterns and an overall shortening of 3′-UTRs during differentiation and upon homeostatic or stress-induced transition from quiescence to proliferation. Specifically, we show that APA regulates activation-induced Glutaminase (Gls) isoform switching by Nudt21. This adaptation of the glutamine metabolism by increasing the GAC:KGA isoform ratio fuels versatile metabolic pathways necessary for HSC self-renewal and proper stress response. Our study establishes APA as a critical regulatory layer orchestrating HSC self-renewal, behavior, and commitment.
Gesehen am 06.04.2020